Life course learning experiences and infant feeding practices in rural Rwanda. Issue 2 (6th January 2021) - Ahishakiye, Jeanine; Vaandrager, Lenneke; Brouwer, Inge D.; Koelen, Maria
Abstract: Most studies about infant and young child feeding (IYCF) practices are often perceived as an individual choice depending on mothers' or caregivers' knowledge or attitudes and are focused on mothers' failure rather than successes in adequately feeding their children. However, the role of life course experiences in IYCF is less investigated. Applying a Salutogenic Model of Health, this study on 14 mothers looks at women's life course learning experiences shaping appropriate IYCF practices during the first year of child's life in a rural district of Rwanda. Transcripts from in‐depth interviews were analysed using thematic analysis. Results indicate that positive social interaction with parents or grandmothers during childhood such as sharing meals, parental role models for dietary choices and cooking skills gained by participating in household food preparation played a role in shaping appropriate IYCF practices. Negative experiences during childhood also had a positive influence on IYCF practices for some participants by converting life course constraints into learning opportunities. Motherhood increased mothers' sense of responsibility over their children's health and nutrition. Moreover, mothers' participation in community cooking classes and role modelling approach were strong avenues that enabled their learning through positive interactions and encouragement. Nutrition promotion interventions should consider tailoring nutrition advice to the complexity of mothers' life course experiences by creating opportunities for positive learning experiences of appropriate IYCF practices.